2020
DOI: 10.3390/s20133744
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Analysis of Commercial Inks by Laser-Induced Breakdown Spectroscopy (LIBS)

Abstract: Laser-induced breakdown spectroscopy (LIBS) was tested for all of the relevant issues in forensic examinations of commercial inks, including classification of pen inks on one paper type and on different paper types, determination of the deposition order of layered inks, and analysis of signatures and toners on one questioned document. The scope of this work was to determine the potential of a single LIBS setup that is compatible with portable instruments for different types of ink analysis, rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The analysis of spectroscopy has been developed to become crucial in the development of forensic science. The study of Cicconi et al, [9] used LIBS for testing issues related to the commercial inks. The study performed classification on pen inks for one paper type and various paper types, determination of the deposition order of layered inks.…”
Section: A Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of spectroscopy has been developed to become crucial in the development of forensic science. The study of Cicconi et al, [9] used LIBS for testing issues related to the commercial inks. The study performed classification on pen inks for one paper type and various paper types, determination of the deposition order of layered inks.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…http:// journals.uob.edu.bh Cicconi et al, [9] Documents with Signatures LIBS spectroscopy Needs complex computations Ameh and Ozovehe [10] Printed Documents FT-IS Needs Complex Computations Zieba et al, [11] Degraded Papers Infrared and Raman Complex to implement due to 2D correlations Buzzini et al, [12] Inkjet Printer Inks Micro-Raman High computational cost due to several technologies involved. Borba et al, [13] Blue Ballpoint Pen Inks PCA, HCA, and PLS-DA Needs complex computations Zieba and Kunicki [14] Several Types of Inks Micro-FTIR, Raman, and XRF Lead to the destruction of the examined document.…”
Section: B the Proposed Approachmentioning
confidence: 99%
“…A recent pan-European forensic round robin study on document forgery reported comparative results regarding the discrimination of papers, pen signatures, and toners by various analytical tools where only LIBS provided all correct responses in the blind test [ 5 ]. In studies of the questioned documents, determining the chronology of deposition of inks on paper is of outmost importance, and this task, difficult also for complex laboratory instruments [ 9 ], has been achieved by LIBS [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of written documents in the modern age of technology has declined, handwritten signatures and notes continue to be widely utilized by the public as proof of consent [2]. Forged signatures and hand-written alterations on legal documents are still issue in civil and criminal investigations [2,3]. Therefore, ink analysis of these documents has become indispensable in the field of document examination.…”
Section: Introductionmentioning
confidence: 99%